Aln ceramic material for semiconductor heater components and method of manufacturing the same

CN123022651APending Publication Date: 2026-10-30MECARO CO LTD(KR)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580016174.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-24
Filing Date
2025-04-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

若不添加氧化钇,就很难实现致密化、减少气孔率、提高热导率、改善结合特性;但添加此类元素时,在一定添加量范围内可提高气体的体积电阻率,但会在气体中形成氧空位和YAG、YAM等氧化钇二元氧化物,进而降低高温下的体积电阻率,增加漏电流

Benefits of technology

[0028]本发明可以提供一种即使在高温下也具有优异体积电阻率的用于半导体加热器部件的AlN陶瓷材料及其制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022651A_ABST
    Figure CN123022651A_ABST
Patent Text Reader

Abstract

The present invention relates to an AlN ceramic material for a semiconductor heater component and a method of manufacturing the same, and the AlN ceramic material for a semiconductor heater component of the present invention includes titanium nitride (TiN), magnesium aluminate (MgAl2O4), and aluminum nitride (AlN).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an AlN ceramic material for semiconductor heater components and a method for manufacturing the same. Background Technology

[0002] With advancements in semiconductor components and manufacturing processes, process temperatures have been continuously increasing, and the types of chemicals used have become more diverse, making process conditions even more stringent. In semiconductor manufacturing, aluminum nitride (AlN) ceramic materials are commonly used as heater components due to their similar coefficient of thermal expansion to Si wafers, excellent thermal conductivity, insulation properties, plasma resistance, and high volume resistivity.

[0003] Despite the excellent properties of AlN ceramic materials, their difficulty in sintering makes them unsuitable for sintering as a single raw material. Additives must be added to improve sintering density and thermal conductivity. Existing companies producing AlN ceramic heaters use various additives to increase density, reduce porosity, improve thermal conductivity, and enhance bonding properties, thereby producing materials with excellent sintering density / thermal conductivity. The most representative additive is yttrium oxide, with different manufacturers using varying amounts. Without yttrium oxide, it is difficult to achieve densification, reduce porosity, improve thermal conductivity, and enhance bonding properties. However, while adding this element can increase the volume resistivity of the gas within a certain range, it also creates oxygen vacancies and yttrium oxide binary oxides such as YAG and YAM, thereby reducing volume resistivity at high temperatures and increasing leakage current.

[0004] Leakage current caused by the decrease in volume resistivity at high temperatures in semiconductor manufacturing processes can affect semiconductor wafers and reduce yield. This phenomenon is a common characteristic of ceramic materials where volume resistivity decreases with increasing temperature. As AlN materials experience a decrease in volume resistivity and an increase in leakage current at high temperatures, the wafer chucking force weakens, ultimately leading to defects such as wafer detachment.

[0005] As semiconductor manufacturing process temperatures rise above 500°C, the number of high-temperature processes requiring ceramic heaters is increasing, necessitating the development of ceramic heaters with high resistance characteristics to minimize leakage current at high temperatures.

[0006] The background technology described herein is something that the inventors have mastered or learned during the development of this invention, and should not be construed as necessarily being a generally known technology disclosed before the application for this invention. Summary of the Invention

[0007] Technical problems to be solved

[0008] To address the aforementioned problems, this invention aims to provide an AlN ceramic material for semiconductor heater components that exhibits excellent volume resistivity even at high temperatures, and a method for manufacturing the same.

[0009] However, the technical problem to be solved by the present invention is not limited to the topics mentioned above, and other topics not mentioned will be clearly understood by those skilled in the art through the following description.

[0010] Technical means to solve the problem

[0011] The AlN ceramic material for semiconductor heater components according to the present invention comprises titanium nitride (TiN), magnesium aluminate (MgAl2O4), and aluminum nitride (AlN).

[0012] According to one embodiment, the AlN ceramic material used for the semiconductor heater component is free of yttrium oxide.

[0013] According to one embodiment, the semiconductor heater component is a semiconductor heater plate, a semiconductor heater shaft, or both.

[0014] According to one embodiment, the magnesium aluminate (MgAl2O4) exists as a second phase in the Mg-Al-O system.

[0015] According to one embodiment, the X-ray diffraction (XRD) peaks of the second phase comprising two or more Mg-Al-O systems are described, wherein the 2θ value of the XRD diffraction peaks is 44° to 46°.

[0016] According to one embodiment, the XRD diffraction peaks do not have yttrium oxide XRD diffraction peaks with 2θ values ​​of 28° to 30° or 33° to 35°.

[0017] According to one embodiment, the grain size is 1.5 μm to 2.5 μm.

[0018] According to one embodiment, the high-temperature resistance value above 500°C is 1.0E+8Ω·cm to 1.0E+10Ω·cm.

[0019] According to one embodiment, the resistance value at room temperature is 1.0E+10Ω·cm to 1.0E+12Ω·cm.

[0020] According to one embodiment, the relative density is 99.5% to 100.5%.

[0021] According to one embodiment, the porosity is 0.02% to 0.2%.

[0022] According to one embodiment, the thermal conductivity is 80 W / mK to 95 W / mK at room temperature and 40 W / mK to 50 W / mK at high temperatures above 500°C.

[0023] A method for manufacturing an AlN ceramic material for a semiconductor heater component according to an embodiment includes the following steps: mixing titanium dioxide (TiO2), magnesium oxide (MgO), and aluminum nitride (AlN) to form a composite powder; and sintering the composite powder.

[0024] According to one embodiment, based on 100 parts by weight of the composite powder, the titanium dioxide (TiO2) content is 0.2 parts by weight to 0.5 parts by weight, and based on 100 parts by weight of the composite powder, the magnesium oxide (MgO) content is 0.2 parts by weight to 1.5 parts by weight.

[0025] According to one embodiment, the sintering step is performed at a temperature of 1500°C to 2000°C.

[0026] According to one embodiment, the sintering step is performed by pressure sintering at a unit area pressure of 5 MPa to 25 MPa.

[0027] Invention Effects

[0028] The present invention provides an AlN ceramic material for semiconductor heater components that exhibits excellent volume resistivity even at high temperatures, and a method for manufacturing the same.

[0029] Specifically, the AlN ceramic material of this invention exhibits excellent volume resistivity at high temperatures above 500°C, and can also solve the problem of performance and yield degradation caused by leakage current. Furthermore, it exhibits excellent bonding and thermal conductivity even without the addition of substances such as yttrium oxide. Attached Figure Description

[0030] Figure 1 The results are XRD analysis results according to embodiments of the present invention.

[0031] Figure 2a and 2b These are the XRD analysis results of the embodiments and comparative examples of the present invention.

[0032] Figure 3 This is a graph showing the relative density, porosity, and grain size of the embodiments and comparative examples of the present invention.

[0033] Figure 4 This is a graph showing the volume resistivity of embodiments and comparative examples of the present invention.

[0034] Figure 5a and Figure 5bThis is a comparison chart of grain size and volume resistivity in embodiments and proportions of the present invention. Detailed Implementation

[0035] The embodiments will now be described in detail with reference to the accompanying drawings. It should be understood that various modifications can be made to the embodiments, and the scope of this application is not limited to the embodiments described below. All modifications to the embodiments, their equivalents, and even their substitutes are within the scope of this invention.

[0036] The terminology used in this invention is for illustrative purposes only and is not intended to limit the scope. Unless otherwise specified in the text, singular expressions include plural meanings. In this specification, terms such as "comprising" or "having" are used to indicate the presence of the features, numbers, steps, operations, constituent elements, accessories, or combinations thereof described in the specification, and do not exclude the possibility of the presence or addition of one or more other features, numbers, steps, operations, constituent elements, accessories, or combinations thereof.

[0037] Unless otherwise defined, all terms used herein, including technical or scientific terms, shall have their ordinary meanings as understood by one of ordinary skill in the art. Terms commonly used, such as those defined in dictionaries, shall be understood as having their meanings in the relevant technical context and shall not be interpreted as idealized or overly formalized meanings unless explicitly defined in this specification.

[0038] Furthermore, in the description with reference to the accompanying drawings, the same reference numerals are used for the same constituent elements regardless of the drawing numbers, and repeated descriptions are omitted. In the description of embodiments, detailed descriptions of relevant well-known technologies are omitted when it is determined that such detailed descriptions would unnecessarily obscure the embodiments. Moreover, when describing the constituent elements of embodiments, terms such as first, second, A, B, (a), and (b) may be used. These terms are only used to distinguish one constituent element from other constituent elements and are not used to limit the nature or order of the corresponding constituent elements. When it is stated that a component is "connected," "linked," or "attached" to another component, it should be understood that a component can be directly connected or attached to another component, and intermediate components can also be "connected," "linked," or "attached" to that component.

[0039] When a constituent element has a common function with a constituent element of a certain embodiment, the same name is used in other embodiments for description. Unless otherwise stated, the description of one embodiment is applicable to other embodiments, and detailed descriptions of repeated content may be omitted.

[0040] The AlN ceramic material for semiconductor heater components of the present invention includes titanium nitride (TiN), magnesium aluminate (MgAl2O4), and aluminum nitride (AlN).

[0041] In semiconductor manufacturing equipment, semiconductor heaters are used to heat wafers while holding them in place during the semiconductor manufacturing process. These heaters can be made of ceramic materials and may include a ceramic substrate and a heating element that generates heat. The ceramic substrate must possess plasma resistance and high volume resistivity at both low and high temperatures to maintain stable production during wafer deposition, requiring excellent electrical insulation and thermal conductivity. Since aluminum nitride (AlN) is stable at high temperatures and possesses excellent electrical insulation and thermal conductivity, ceramic materials containing AlN can be used as the main component of ceramic substrates. However, the volume resistivity of aluminum nitride decreases with increasing temperature. Therefore, for ceramic heaters using aluminum nitride, the decrease in volume resistivity of the ceramic substrate with increasing temperature can potentially cause leakage current. Furthermore, in recent semiconductor manufacturing processes, the continuously increasing process temperatures have led to a rapid decrease in the volume resistivity of aluminum nitride ceramic heaters, resulting in leakage current. Therefore, it is necessary to find methods to overcome this problem and maintain the volume resistivity of the ceramic material at high temperatures.

[0042] The AlN ceramic material for semiconductor heater components of the present invention comprises titanium nitride and magnesium aluminate, exhibiting excellent volume resistivity and high resistance characteristics at high temperatures, which can solve the problem of performance and yield degradation caused by leakage current.

[0043] The titanium nitride may be a second phase formed from titanium dioxide (TiO2), and the magnesium aluminate may be a second phase formed from magnesium oxide (MgO).

[0044] According to one embodiment, the AlN ceramic material used for the semiconductor heater component may be yttria-free.

[0045] Existing AlN ceramic materials used in semiconductor heater components are made by adding yttrium oxide, thereby improving density, reducing porosity, increasing thermal conductivity, and improving bonding properties. However, the addition of yttrium oxide generates yttrium oxide second phases such as oxygen vacancies, YAG, and YAM, which can increase leakage current at high temperatures. This invention provides an AlN ceramic material that, as a yttrium oxide-free ceramic material, exhibits excellent volume resistivity at high temperatures without the bonding performance issues.

[0046] According to one embodiment, the semiconductor heater component may be a plate of a semiconductor heater, a shaft of a semiconductor heater, or both.

[0047] The AlN material of the present invention can be applied to the plate only, the shaft only, or both in a semiconductor heater consisting of a plate and a shaft.

[0048] According to one embodiment, the magnesium aluminate (MgAl2O4) can exist as a second phase in the Mg-Al-O system.

[0049] The second phase can be confirmed by diffraction peaks in the XRD pattern measured using CuKα rays at 40 kV / 40 mA.

[0050] According to one embodiment, the present invention may include two or more XRD diffraction peaks of the second phase of the Mg-Al-O system, wherein the 2θ value of the XRD diffraction peaks may be 44° to 46°.

[0051] The XRD diffraction peaks representing the second phase of the Mg-Al-O system can be two or more. This is because MgO is uniformly distributed and reacts within the material, forming a certain amount or more of the Mg-Al-O phase. Preferably, two XRD diffraction peaks can be identified, and the 2θ value of at least one of the XRD diffraction peaks can be between 44° and 46°.

[0052] Figure 1 These are the XRD analysis results according to an embodiment of the present invention. (Reference) Figure 1 The diffraction peaks of the two Mg-O-Al second phases and the TiN second phase can be confirmed.

[0053] According to one embodiment, the 2θ value of the XRD diffraction peak of the TiN second phase can be 42° to 44°.

[0054] The ratio of the diffraction peak intensity of titanium nitride to that of aluminum nitride (TiN / AlN) can be 0.05% to 1%, and the ratio of the diffraction peak intensity of the second phase of the Mg-Al-O system to that of aluminum nitride (MgAl2O4 / AlN) can be 0.05% to 6%.

[0055] Compared to the main peak of aluminum nitride, when the second phase of titanium nitride and Mg-Al-O exhibits diffraction peak intensities within the aforementioned range, it can show an increase in intensity caused by TiN and an increase in resistivity caused by Mg-Al-O, while preventing a decrease in volume resistivity caused by TiN and a decrease in thermal conductivity caused by Mg-Al-O.

[0056] According to one embodiment, the XRD diffraction peaks may not have XRD diffraction peaks of the yttrium oxide system with 2θ values ​​of 28° to 30° or 33° to 35°.

[0057] The AlN ceramic material of this invention exhibits no yttrium oxide-based XRD diffraction peaks in its XRD pattern, meaning no diffraction peaks of the yttrium oxide-based second phase are observed. In other words, since no yttrium oxide additive is added during the manufacture of the AlN ceramic material, no yttrium oxide-based second phase is formed, resulting in the absence of yttrium oxide-based XRD diffraction peaks. Because no XRD diffraction peaks are detected within the 2θ range of 28° to 30° or 33° to 35°, it can be confirmed that it does not contain yttrium oxide and that it does not contain a γ-Al-O second phase.

[0058] The preferred XRD measurement conditions are an accelerating voltage / current of 40 kV / 40 mA, CuK α rays (wavelength 1.54060 nm), a scanning speed of 1° / min, and a 2θ range of 10° to 80°.

[0059] According to one embodiment, the grain size can be from 1.5 μm to 2.5 μm.

[0060] The grain size, measured by EBSD, is likely related to the density of grain boundaries (the boundaries between grains). As grains become smaller, grain boundaries increase, leading to larger potential wells that can impede charge movement. Furthermore, grain size is related to thermal conductivity, and a certain level of thermal conductivity may be required to reduce temperature distribution deviations in the heater.

[0061] The grain size is preferably 1.5 μm to 2.0 μm, or 2.0 μm to 2.5 μm. If the grain size exceeds the range, there may be a problem of reduced high-temperature volume resistivity.

[0062] The preferred measurement conditions for the grains are as follows: after mirror polishing to achieve a sample roughness of Ra 0.09 to 0.03, the mapped image is captured at 2000x magnification and 20kV accelerating voltage. The final grain size is the median obtained based on the grain boundary of the captured image.

[0063] According to one embodiment, the high-temperature resistance value above 500°C can be from 1.0E+8Ω·cm to 1.0E+10Ω·cm.

[0064] Preferably, the resistance value can be measured using an AC resistor at a high temperature of 500°C to 650°C. Specifically, the analytical sample used for resistance measurement can be made into a disk shape, with platinum (Pt) coated electrodes formed at its top and bottom ends, thereby performing the measurement. The measurement range is 10 kHz to 10 mHz, and the E range is -10 V to 10 V, increasing from room temperature to 500°C in 100°C increments. The temperature is measured after reaching and maintaining the measurement temperature for 5 minutes to minimize resistance characteristic errors caused by temperature changes.

[0065] If the high-temperature resistance value is below the specified range, leakage current between the mesh and the molybdenum (Mo) heating wire cannot be blocked, causing the heater to malfunction and affecting the stable production of the CVD process. Specifically, the resistance value of traditional AlN ceramic materials decreases at high temperatures, leading to leakage current between the electrostatically charged mesh and the Mo heating wire. If this leakage current moves along the radio frequency (RF) mesh direction, the RF mesh cannot perform its functions such as wafer chucking and grounding in plasma processes. Compared to traditional AlN materials, the AlN ceramic material of this invention exhibits a higher high-temperature resistance value within the specified range, thereby blocking the leakage current between the mesh and the Mo heating wire, enabling the heater to operate stably, and thus achieving stable production in the CVD process. This solves the problem of performance and yield degradation caused by leakage current.

[0066] According to one embodiment, the room temperature resistance value can be from 1.0E+10Ω·cm to 1.0E+12Ω·cm.

[0067] The room temperature can be between 15°C and 25°C.

[0068] The heater can be operated when the room temperature resistance value is within the stated range. If it is below the stated range, the heater may be unusable due to excessive impurities.

[0069] According to one embodiment, the relative density can be between 99.5% and 100.5%.

[0070] The relative density is the density of the AlN ceramic material of the present invention, determined by the Archimedes method, expressed as AlN 100% (3.26 g / cm³). 3 The relative density is compared to the theoretical density of [a specific product / component]. If the relative density is lower than the specified range, problems such as reduced mechanical properties and thermal conductivity may occur due to decreased sinterability. When the relative density is within the specified range, there will be no heater operation problems when using the product.

[0071] According to one embodiment, the porosity can be from 0.02% to 0.2%.

[0072] Porosity is formed during sintering due to the filling of voids by the movement and diffusion of powder particles within the sintering temperature range. A porosity close to 0 indicates a single-crystal state. Preferably, the porosity is 0.02% to 0.15%; 0.02% to 0.1%; 0.02% to 0.05%; 0.05% to 0.2%; 0.05% to 0.15%; 0.05% to 0.1%; 0.1% to 0.2%; 0.1% to 0.15%; or 0.15% to 0.2%.

[0073] If the porosity is below the specified range, potential energy wells will not exist due to the absence of grain boundaries, potentially leading to a decrease in volume resistivity. Conversely, if the porosity exceeds the specified range, the significantly increased porosity may degrade the structural ceramic properties. When the porosity is within the specified range, heater operation problems will not occur during product use.

[0074] According to one embodiment, the thermal conductivity at room temperature can be from 80 W / mK to 95 W / mK, while at high temperatures above 500°C, the thermal conductivity can be from 40 W / mK to 50 W / mK.

[0075] If the thermal conductivity is below the specified range, it will lead to decreased relative density, increased porosity, and reduced mechanical properties due to poor sinterability; if it exceeds the specified range, it may increase grain size, decrease grain boundary density, and cause a decrease in volume resistivity. In particular, in order to minimize the temperature distribution deviation of the heater (below 10°C at 500°C), a certain level of thermal conductivity is required even at high temperatures, therefore, the thermal conductivity within the specified range is preferred.

[0076] The present invention provides a method for manufacturing AlN ceramic material for semiconductor heater components, comprising the following steps: mixing titanium dioxide (TiO2), magnesium oxide (MgO), and aluminum nitride (AlN) to form a composite powder; and sintering the composite powder.

[0077] The step of forming the composite powder may be to add titanium dioxide powder and magnesium oxide powder to aluminum nitride powder and mix them by dry or wet method.

[0078] To maintain the volume resistivity of ceramic materials at high temperatures, metallic additives can be added to aluminum nitride. However, these metallic additives may reduce the thermal conductivity of the ceramic heater, leading to poor temperature uniformity. The AlN ceramic material manufacturing method of this invention solves these problems by forming a composite powder or granules containing appropriate amounts of titanium dioxide and magnesium oxide. Adding a small amount of titanium dioxide increases resistance, while magnesium oxide increases volume resistivity by forming a composite material. Furthermore, by not adding yttrium oxide, the potential thermal conductivity variations that may occur when forming second phases such as YAG and YAM to generate resistance and thermal conductivity with Mg and Ti are eliminated, thus ensuring stable material manufacturing.

[0079] According to one embodiment, based on 100 parts by weight of the composite powder, the content of titanium dioxide (TiO2) can be from 0.2 parts by weight to 0.5 parts by weight, and based on 100 parts by weight of the composite powder, the content of magnesium oxide (MgO) can be from 0.2 parts by weight to 1.5 parts by weight.

[0080] Increasing the titanium dioxide content reduces the high-temperature electrical resistance of AlN ceramic materials; while increasing the magnesium oxide content reduces grain size, improves high-temperature electrical resistance, or increases porosity. Therefore, it is necessary to form appropriate composite powders to react with AlN within a suitable content range.

[0081] If the titanium dioxide content is below the specified range, it exists in the material as Ti, existing only in a state that does not affect the material itself, and therefore its phase may not be identifiable; if it exceeds the specified range, due to the low resistance characteristics of TiN, it will reduce the overall resistance of the material, leading to a decrease in volume resistivity at high temperatures.

[0082] If the magnesium oxide content exceeds the aforementioned range, it may volatilize during sintering, forming numerous micropores, which in turn causes problems with material properties such as decreased density, increased porosity, and reduced structural characteristics and thermal conductivity. The preferred magnesium oxide content is 0.2 parts by weight to 1.0 parts by weight; 0.2 parts by weight to 0.5 parts by weight; 0.5 parts by weight to 1.5 parts by weight; 0.5 parts by weight to 1.0 parts by weight; or 1.0 parts by weight to 1.5 parts by weight.

[0083] According to one embodiment, the sintering step can be performed at a temperature of 1500°C to 2000°C.

[0084] Through the aforementioned sintering, AlN ceramic materials for semiconductor heater components containing a second phase of TiN and Mg-Al-O system can be manufactured.

[0085] Preferably, the process can be carried out at a temperature of 1600°C to 2000°C, or 1600°C to 1900°C, or 1700°C to 1900°C.

[0086] If the sintering temperature is below the specified range, densification cannot be achieved during sintering, which may result in problems such as reduced density, increased porosity, decreased structural physical properties, and reduced thermal conductivity. If the temperature exceeds the specified range, problems such as increased grain size, reduced grain boundaries, and decreased volume resistivity may occur.

[0087] According to one embodiment, the sintering step may be performed under pressure sintering at a unit area pressure of 5 MPa to 25 MPa.

[0088] The pressure sintering is a sintering process condition used to achieve densification under yttrium oxide-free conditions.

[0089] Preferably, pressure sintering can be performed at pressures of 5 MPa to 20 MPa; 5 MPa to 15 MPa; 5 MPa to 10 MPa; 10 MPa to 25 MPa; 10 MPa to 20 MPa; 10 MPa to 15 MPa; 15 MPa to 25 MPa; 15 MPa to 20 MPa; or 20 MPa to 25 MPa.

[0090] If the pressure is below the specified range, problems such as decreased density, increased porosity, and decreased thermal conductivity may occur; if it exceeds the specified range, heater performance problems such as deformation (closer proximity) of the distance between the heater and the grid, increased leakage current, and deformation of heat distribution may occur.

[0091] The present invention will now be described in more detail through examples and comparative examples.

[0092] However, these embodiments are only used to illustrate the invention in more detail, and the scope of the invention is not limited thereto.

[0093] Example

[0094] AlN ceramic materials for semiconductor heater components were manufactured by sintering a composite powder of mixed titanium dioxide (TiO2), magnesium oxide (MgO), and aluminum nitride (AlN). The compositions of the examples and comparative examples are shown in Table 1 below. Table 2 below shows the analytical results of the second phases of the TiN and Mg-Al-O examples where the second phases were confirmed.

[0095] Table 1

[0096]

[0097] Table 2

[0098]

[0099] As shown in Table 1 above, the second phase of the examples and comparative examples was confirmed. In the comparative example with added yttrium oxide, Y-Al-O was confirmed as the second phase.

[0100] Figure 2a and Figure 2b The XRD analysis results of embodiments and comparative examples of the present invention are shown. XRD diffraction peak measurements confirmed the crystal properties of the AlN ceramic material, confirming the formation of a second phase consisting of TiN and Mg-Al-O systems.

[0101] refer to Figure 2a , Figure 2b As shown in Table 2, XRD diffraction peaks of Mg-Al-O were confirmed in the composite powder phase within the range of 0.5 / 1 / 1.5 wt% MgO content, and these peaks occurred between 36° and 38° and 44° and 46° of 2-theta (2θ). Particularly in the XRD, the second diffraction peak (2nd Peak) of Mg-Al-O occurring between 44° and 46° can be considered characteristic of the high-temperature composition of the AlN ceramic material of this invention. That is, the presence of only one main peak indicates formation only at the seed level, while the presence of multiple diffraction peaks of the Mg-Al-O phase indicates the formation of a phase with a certain or greater distribution. In summary, the presence of multiple diffraction peaks of the Mg-Al-O phase indicates the formation of a greater proportion of the Mg-Al-O phase, which may be influenced by process conditions such as the amount and dispersibility of MgO. Furthermore, it was confirmed that the intensity of the diffraction peaks (intensity ratio compared to the AlN main peak) increased with increasing MgO content, and a preferred range of less than 6% compared to the AlN main peak was observed.

[0102] XRD diffraction peaks of TiN were confirmed in the composite powder phase with TiO2 content in the range of 0.25 / 0.75 wt%, and occurred between 42° and 44° of 2-theta (2θ). Furthermore, it was confirmed that the diffraction peak intensity increased with increasing TiO2 content (intensity ratio compared to the AlN main peak), and a preferred range of less than 1% compared to the AlN main peak was observed.

[0103] The relative density, porosity, grain size, volume resistivity, and other characteristics of the embodiments and comparative examples are analyzed and shown in Table 3 below. Figure 3 , Figure 4 , Figure 5a , Figure 5b .

[0104] Table 3

[0105]

[0106] The relative density and porosity of the sintering gas must meet the requirements of a relative density of over 99% and a porosity of less than 0.2% to produce structural ceramics. Refer to Table 3 above. Figure 3 It can be confirmed that the compositions of Examples 1 to 3 meet the target relative density and porosity. In particular, the grain growth control effect based on the Mg increment can be confirmed, and a significant crystal growth control effect is confirmed in the range of 0.5 to 1 wt%, but the grain size is similar when reaching the limit of 1 wt% and 1.5 wt%. Porosity tends to increase with increasing Mg content, and it increases significantly when the Mg content is 1.5 wt%. It can be expected that when the Mg content is above this level, the performance of the structural ceramic will decrease due to porosity. Therefore, it can be confirmed that the appropriate limit range for Mg content is below 1.5 wt%.

[0107] To measure volume resistivity, a sample with a thickness of 2 mm and a diameter of 12 mm was prepared. Electrodes made of platinum and formed on the top and bottom of the sample with a diameter of 12 mm were used to form the sample. The measurement was performed using an AC resistor with a voltage of 2.5 V and a frequency of 10 mHz to 10 kHz.

[0108] Refer to Table 3 above and Figure 4 For TiN, when a high-temperature volume resistivity of 1.0E+8 Ω·cm or higher is required, an addition of 0.25 wt% TiO2 in the composite powder is sufficient. Furthermore, the volume resistivity decreases with increasing TiN yield. The composite powder exhibits high-temperature, high-resistivity characteristics within the range of 0.2 to 0.5 wt% TiO2 and 0.2 to 1.5 wt% MgO, satisfying the high-temperature volume resistivity requirement of 1.0E+8 Ω·cm. In other words, in the composite powder formation process, for materials sintered with added TiO2 and MgO, the range where the volume resistivity measured at 500°C meets 1.0E+8 Ω·cm or higher corresponds to the addition of 0.25% TiO2. It can be expected that the volume resistivity will meet 1.0E+8 Ω·cm within the range of 0.2 to 0.5 wt%. Furthermore, for AlN ceramic materials sintered with added Ti and Mg oxides, the range in which the volume resistivity measured within the 500℃ range meets or exceeds 1.0E+8 Ω·cm is the range with 0.25 wt% TiO2 and 0.5 / 1 / 1.5 wt% MgO. It can be expected that the volume resistivity of MgO in the range of 0.2~1.5 wt% will meet or exceed 1.0E+8 Ω·cm.

[0109] When the MgO content is 1 wt%, it exhibits the highest high-temperature volume resistivity characteristics at 500°C, and the high-temperature volume resistivity decreases from 1.5 wt%. It can be expected that the high-temperature resistivity will decrease as the MgO content is further increased. In addition, since the composition of Example 3 shows a trend of increased porosity, it can be determined that it is difficult to obtain the desired effect by increasing the content when the MgO content is above 1.5 wt%.

[0110] refer to Figure 5a and Figure 5b High-temperature volume resistivity based on grain size exhibits a characteristic that increases with decreasing grain size. Specifically, when MgO content is 1 wt%, the grain size is smallest and the high-temperature volume resistivity is highest. With increasing TiO2 content, the grain size decreases, but the high-temperature volume resistivity also decreases, indicating that TiO2 has a greater impact on increasing TiN yield than on reducing grain size.

[0111] In summary, the embodiments have been described with reference to the limited accompanying drawings. Those skilled in the art can make various modifications and variations based on the description. For example, appropriate results can be obtained by performing the described techniques in a different order than the described methods, and / or by combining or integrating the described constituent elements in a different manner than the described methods, or by replacing or substituting them with other constituent elements or equivalents.

[0112] Therefore, other embodiments, other implementations, and equivalents of the claims are all within the scope of the appended claims.

Claims

1. An AlN ceramic material for use in semiconductor heater components, characterized in that, It contains titanium nitride (TiN), magnesium aluminate (MgAl2O4), and aluminum nitride (AlN).

2. The AlN ceramic material for a semiconductor heater component as described in claim 1, characterized in that, The AlN ceramic material used in the semiconductor heater component is free of yttrium oxide.

3. The AlN ceramic material for a semiconductor heater component as described in claim 1, characterized in that, The semiconductor heater component is a plate of a semiconductor heater, or a shaft of a semiconductor heater, or both.

4. The AlN ceramic material for a semiconductor heater component as described in claim 1, characterized in that, The magnesium aluminate (MgAl2O4) exists as the second phase of the Mg-Al-O system.

5. The AlN ceramic material for a semiconductor heater component as described in claim 1, characterized in that, X-ray diffraction (XRD) peaks of a second phase containing more than two Mg-Al-O systems. The 2θ value of the XRD diffraction peak is 44° to 46°.

6. The AlN ceramic material for a semiconductor heater component as described in claim 5, characterized in that, The XRD diffraction peaks do not have yttrium oxide XRD diffraction peaks with 2θ values ​​of 28° to 30° or 33° to 35°.

7. The AlN ceramic material for a semiconductor heater component as described in claim 1, characterized in that, The grain size is 1.5 μm to 2.5 μm.

8. The AlN ceramic material for a semiconductor heater component as described in claim 1, characterized in that, At temperatures above 500℃, the resistance value is 1.0E+8Ω·cm to 1.0E+10Ω·cm.

9. The AlN ceramic material for a semiconductor heater component as described in claim 1, characterized in that, The resistance at room temperature is 1.0E+10Ω·cm to 1.0E+12Ω·cm.

10. The AlN ceramic material for a semiconductor heater component as claimed in claim 1, characterized in that, The relative density is 99.5% to 100.5%.

11. The AlN ceramic material for a semiconductor heater component as claimed in claim 1, characterized in that, The porosity is 0.02% to 0.2%.

12. The AlN ceramic material for a semiconductor heater component as described in claim 1, characterized in that, The thermal conductivity at room temperature is 80 W / mK to 95 W / mK. At temperatures above 500℃, the thermal conductivity is 40W / mK to 50W / mK.

13. A method for manufacturing an AlN ceramic material for a semiconductor heater component, characterized in that, Includes the following steps: A composite powder is formed by mixing titanium dioxide (TiO2), magnesium oxide (MgO), and aluminum nitride (AlN); and The composite powder is then sintered.

14. The method for manufacturing AlN ceramic material for semiconductor heater components as described in claim 13, characterized in that, Based on 100 parts by weight of the composite powder, the titanium dioxide (TiO2) content is 0.2 parts by weight to 0.5 parts by weight. Based on 100 parts by weight of the composite powder, the magnesium oxide (MgO) content is from 0.2 parts by weight to 1.5 parts by weight.

15. The method for manufacturing AlN ceramic material for semiconductor heater components as described in claim 13, characterized in that, The sintering step is performed at a temperature of 1500°C to 2000°C.

16. The method for manufacturing AlN ceramic material for semiconductor heater components as described in claim 13, characterized in that, The sintering step is pressure sintering at a unit area pressure of 5 MPa to 25 MPa.